Titans of the early universe: the Prato statement on the origin of the first supermassive black holes - Woods, Tyrone E.; Agarwal, Bhaskar; Bromm, Volker; Bunker, Andrew; Chen, Ke-Jung; Chon, Sunmyon; Ferrara, Andrea; Glover, Simon; Haemmerlé, Lionel; Haiman, Zoltán; Hartwig, Tilman; Heger, Alexander; et al. (Publications of the Astronomical Society of Australia, 2019)
In recent years, the discovery of massive quasars at - - - $z\sim7$ - - - has provided a striking challenge to our understanding of the origin and growth of supermassive black holes in the early Universe. Mounting observational and theoretical evidence indicates the viability of massive seeds, formed by the collapse of supermassive stars, as a progenitor model for such early, massive accreting black holes. Although considerable progress has been made in our theoretical understanding, many questions remain regarding how (and how often) such objects may form, how they live and die, and how next generation observatories may yield new insight into the origin of these primordial titans. This review focusses on our present understanding of this remarkable formation scenario, based on the discussions held at the Monash Prato Centre from November 20 to 24, 2017, during the workshop ‘Titans of the Early Universe: The Origin of the First Supermassive Black Holes’.